2009
DOI: 10.1111/j.1478-3231.2009.02077.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein–calorie malnutrition as a prognostic indicator of mortality among patients hospitalized with cirrhosis and portal hypertension

Abstract: PCM is more common among patients with cirrhosis and PHTN than the general medical population, and is associated with higher in-hospital mortality and resource utilization. PCM may be an indicator of greater disease severity and should be routinely assessed on admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
125
2
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(140 citation statements)
references
References 34 publications
2
125
2
11
Order By: Relevance
“…For many years, malnutrition has been related to worse clinical outcomes and higher incidence of complications such as ascites, hepatic encephalopathy and infections 22 , hepatorenal syndrome and diabetes mellitus. It is considered a risk factor for morbidity and mortality in short and long term before and after transplantation 23,25 as well as in abdominal surgery 21 . A recent study by Sam and Nguyen 23 showed the association of PCM with longer hospitalization (8.7 days versus 5.7 days, p<0.0001), higher in-hospital mortality and a higher rate of readmissions.…”
Section: Resultsmentioning
confidence: 99%
“…For many years, malnutrition has been related to worse clinical outcomes and higher incidence of complications such as ascites, hepatic encephalopathy and infections 22 , hepatorenal syndrome and diabetes mellitus. It is considered a risk factor for morbidity and mortality in short and long term before and after transplantation 23,25 as well as in abdominal surgery 21 . A recent study by Sam and Nguyen 23 showed the association of PCM with longer hospitalization (8.7 days versus 5.7 days, p<0.0001), higher in-hospital mortality and a higher rate of readmissions.…”
Section: Resultsmentioning
confidence: 99%
“…It might also be associated with protein-losing enteropathies, metabolic disorders and constant restrictive dietetic approaches to which these patients are subjected (34) .…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic disorders, such as alterations in the metabolism of carbohydrates (insulin resistance); proteins, due to increased need and decreased absorption with reduction in hepatic synthesis; and fat, by lipolysis increase and lipid oxidation (34) , as well as hypermetabolism, which occurs in 16%-34% of patients with chronic hepatic disease (32,34) , can favor malnutrition development.…”
Section: Discussionmentioning
confidence: 99%
“…O aumento das citocinas pró-inflamatórias (80) , a anorexia álcool induzida (81) e a deficiência de magnésio e zinco (disgeusia) desencadeiam a hiporexia. (22,36) A presença de ascite (3,81,82) , a gastroparesia (81) , a motilidade alterada do trato gastrointestinal (81) e o supercrescimento bacteriano (81) associado podem determinar a ocorrência de náuseas e de saciedade precoce. Cerca de 45% dos pacientes cirróticos apresentam infecção coexistente por Helicobacter pylori com a conseqüente ocorrência de dispepsias.…”
Section: Discussionunclassified
“…(83) Os fenômenos de má digestão e disabsortivos estão relacionados à má absorção de gordura devido à redução na síntese de ácido biliar. (81) A colestase e a hipertensão portal podem influenciar a digestão e a absorção de nutrientes (80) , como por exemplo, das gorduras e das vitaminas lipossolúveis, resultando em deficiências específicas de vitamina A; osteoporose como resultado da perda de cálcio e má absorção de vitamina D, deficiência de folato, riboflavina, nicotinamida, ácido pantotênico, piridoxina, vitamina B12 e tiamina. (84,85) A possibilidade da coexistência da doença hepática com a enteropatia perdedora de proteína (81,86) , a doença inflamatória intestinal, a insuficiência pancreática decorrente do alcoolismo crônico e a atrofia das vilosidades intestinais podem contribuir para a má absorção e utilização de nutrientes.…”
Section: Discussionunclassified